Program pembiasaan berbahasa Arab di MTs Pondok Pesantren Al-Ma'tuq Sukabumi - Rosyadi, Sabila; Alim, Akhmad (Tawazun: Jurnal Pendidikan Islam, 2022)
The Arabic-speaking environment has an important role in the development of science and student learning materials in the classroom. The lack of extracurricular activities that can support the ability of students to form an Arabic-speaking environment and the low tendency of students to Arabic, even many of them have the impression that learning Arabic is more difficult than learning other foreign languages, are factors of the problem. in the development of the Arabic language of students. In addition, the concern of an educator who is limited to learning in the classroom, without paying attention to the habituation of Arabic in his environment, is a separate problem factor in the habit of speaking Arabic. With this background, the author is interested in researching Arabic language habituation programs that can form students' habits of speaking Arabic easily. The focus of the research is on Islamic boarding schools; namely MTs Pesantren Al-Ma'tuq Sukabumi. In this study, the author uses a type of qualitative research, namely by collecting data obtained from observations, interviews, documentation, analysis, field notes. Researchers perform data analysis by multiplying information, looking for relationships to various sources, comparing, and finding results on the basis of actual data. After doing the research, the results obtained: the concept of the Arabic language habituation program at MTs Pondok Pesantren Al-Ma'tuq. This started from the purpose of Arabic language habituation, the planning process, activity programs, and evaluation techniques for evaluating activity programs. This study recommends educational institutions and educators to implement Arabic language habituation programs for students in the school environment. Abstrak Lingkungan berbahasa Arab memiliki peran penting dalam pengembangan keilmuan dan materi pembelajaran siswa di dalam kelas. Minimnya kegiatan-kegiatan ekstrakurikuler yang dapat menunjang kemampuan peserta didik dalam membentuk lingkungan berbahasa Arab serta kecenderungan peserta didik yang rendah terhadap bahasa Arab, bahkan banyak di antara mereka yang memiliki kesan bahwa belajar bahasa Arab itu lebih sulit dibandingkan dengan belajar bahasa asing lainnya, menjadi faktor permasalahan dalam pengembangan bahasa Arab peserta didik. Selain itu, kepedulian seorang pendidik yang terbatas pada pembelajaran di kelas, tanpa memperhatikan pembiasaan berbahasa Arab di lingkungannya, menjadi faktor permasalahan tersendiri dalam pembiasaan berbahasa Arab. Dengan latar belakang tersebut, penulis tertarik untuk meneliti program-program pembiasaan berbahasa Arab yang dapat membentuk kebiasaan peserta didik berbicara bahasa Arab dengan mudah. Fokus penelitian tersebut berada di pesantren; yaitu MTs Pesantren Al-Ma'tuq Sukabumi. Dalam penelitian ini, penulis menggunakan jenis penelitian kualitatif, yaitu dengan mengumpulkan data yang didapat dari hasil pengamatan, wawancara, dokumentasi, analisis, catatan lapangan. Peneliti melakukan analisis data dengan memperbanyak informasi, mencari hubungan ke berbagai sumber, membandingkan, dan menemukan hasil atas dasar data sebenarnya. Setelah dilakukan penelitian diperoleh hasil: konsep program pembiasaan berbahasa Arab di MTs Pondok Pesantren Al-Ma'tuq. Hal tersebut berawal dari tujuan pembiasaan berbahasa Arab, proses perencanaan, program-program kegiatan, serta teknik evaluasi penilaian program kegiatan. Penelitian ini merekomendasikan kepada lembaga pendidikan dan para pendidik, agar menerapkan program pembiasaan berbahasa Arab kepada peserta didik di lingkungan sekolah.